2017
DOI: 10.6061/clinics/2017(06)08
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of first-generation protease inhibitors in real-world patients with hepatitis C virus genotype 1 infection in Brazil: a multicenter study

Abstract: OBJECTIVE:To evaluate the effectiveness and safety of first-generation protease inhibitors for the treatment of genotype 1 hepatitis C virus-infected patients at Brazilian reference centers.METHODS:This multicenter cross-sectional study included hepatitis C virus genotype 1 monoinfected patients treated with Peg-interferon, ribavirin, and either boceprevir (n=158) or telaprevir (n=557) between July 2013 and April 2014 at 15 reference centers in Brazil. Demographic, clinical, virological, and adverse events dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
2
0
9

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 27 publications
(65 reference statements)
3
2
0
9
Order By: Relevance
“…Our results were similar to the findings of the French cohort and other studies conducted by Brazilian researchers [14][15][16]18 . In addition, the rates of treatment cessation because of intolerance or side effects were very high and medications were not well tolerated by the majority of the subjects.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results were similar to the findings of the French cohort and other studies conducted by Brazilian researchers [14][15][16]18 . In addition, the rates of treatment cessation because of intolerance or side effects were very high and medications were not well tolerated by the majority of the subjects.…”
Section: Discussionsupporting
confidence: 92%
“…More than half of the patients had failed to reach SVR in a previous treatment. For the triple therapy, 54.2% of patients reached SVR, which was similar to that reported by other Brazilian authors 16,18 . Our findings suggested that the attainment of SVR was lower in patients with advanced fibrosis than that reported in the initial studies.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…There are few published, real-life studies that have evaluated the use of first-generation PIs in Latin America, particularly in Brazil [7][8][9] . Thus, this study was aimed at analyzing the safety and effectiveness of the above-mentioned triple regimens, in addition to sharing the experience of a referral center established at a tertiary/quaternary university hospital in Southeastern Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Além disso, foram relatadas reações adversas severas em 40% dos pacientes do estudo, como hospitalizações, infecções severas, descompensação da doença hepática, alterações dermatológicas, cutâneas e morte(HÉZODE et al, 2013). Verificou-se taxa de RVS média de 56,6% (51,9% para BOC e 58% para TVR) e reações adversas severas ocorreram em 44,2% dos pacientes, com seis mortes registradas(CALLEFI et al, 2017). Em outro estudo multicêntrico brasileiro, realizado por Lobato e colaboradores, encontrou-se taxa global de RVS de 54,2% e observou-se ocorrência de reações adversas em 87,5% dos pacientes(LOBATO et.…”
unclassified